Improving family caregiver understanding of range of motion exercises for community-based stroke care: A pre-experimental study within the clinical pathway - Mira Asmirajanti; Rini Handayani; Dwi Nurmawaty; Yulhendri (Physical Therapy Journal of Indonesia, 2026)
Background: Family caregivers play a crucial role in the recovery of stroke patients, especially in community settings. An adequate understanding of the range of motion (ROM) exercises enables caregivers to actively support rehabilitation and prevent complications. This study aimed to analyze the improvement of family caregivers' understanding of ROM exercises after training. Methods: This pre-experimental one-group pretest-posttest study involved 25 families with stroke patients for ≥1 month, selected through consecutive sampling in the working area of Puskesmas Tambora, West Jakarta, in July 2025. Interventions included active and passive ROM exercises based on standard operating procedures (SOPs), also it was used to simulate the manual muscle testing (MMT). Measurement instruments used the validity and reliability questionnaires and MMT observation sheets. Data were analyzed by the Wilcoxon test at a significance level of p<0.05. Results: The results showed a significant increase in family caregiver understanding of ROM (p= 0.000). Before the training, 88% of respondents (22 people) had sufficient knowledge, and 12% (3 people) had good knowledge. After the training, the proportion of good knowledge increased to 56% (14 people), while moderate knowledge decreased to 44% (11 people). Conclusion: Structured training effectively enhanced family caregivers' understanding of ROM exercises, supporting their active participation in patient care. These findings suggest that such education can be integrated into community-based non-digital clinical pathways to prevent complications in stroke patients.